KERJA SAMA INDONESIA DAN UNICEF DALAM PENGEMBANGAN KUALITAS PENDIDIKAN DI PROVINSI NUSA TENGGARA TIMUR (2016 - 2020) - Siti Nur Firli, (2023)
Poor access to education for children in Nusa Tenggara Timur is a major issue. According to the report, there were only three of four children (age 7-24) in 2016 that had a chance to go to school. On top of that, accessibility for children in early age is also a considerable matter for Nusa Tenggara Timur. As their response towards the issue, the local government of Nusa Tenggara Timur initiating a cooperation with UNICEF. Therefore, this thesis would try to explain how the cooperation was performed with the use of analytic descriptive research in qualitative methods. The result of this thesis revealed that cooperation between Indonesia and UNICEF was carried out through implementation of Country Program Action Plan (CPAP). This cooperation was aimed to support education development in NTT with participation of numerous parties such as ministry, social institutions, and the community